الأداء المالي للموازنة العامة في الجزائر في ظل تغيرات أسعار النفط العالمية للفترة (1970-2021) - بوعلام عيسى; محمد عيسى محمد محمود (جامعة الوادي University of Eloued, 2023)
تهدف الدراسة إلى تقييم الأداء المالي للموازنة العامة في الجزائر في ظل تغيرات أسعار النفط العالمية للفترة (1970-2021)، حيث ركزت الدراسة على التعريف بالموازنة العامة ومكوناتها (النفقات العامة والإيرادات العامة) في التشريع الجزائري، وكذلك التعرف على كيفية أدائها المالي من خلال تتبع مسارها وإبراز علاقتها بتقلبات أسعار النفط في الأسواق العالمية. توصلت الدراسة إلى أن الموازنة العامة تعاني اختلالات هيكلية عميقة، وهذا بسبب اعتمادها بالدرجة الأساس على عائدات الجباية البترولية في تكوين الإيرادات العامة وذلك من أجل المساهمة في تغطية النفقات العامة، الأمر الذي يشكل تهديدا لها ويجعلها عرضة للآثار السلبية التي تعكسها التغيرات السريعة والمفاجئة لأسعار النفط في الأسواق العالمية. The study aims to assess the financial performance of Algeria's general budget in view of the changes in global oil prices for the period 1970-2021. The study focused on the definition of the general budget and its components (public expenditures and public revenues) in Algerian legislation, as well as on how it performs financially by tracking its trajectory and highlighting its relationship with the fluctuations of oil prices in the world markets. The study found that the public budget suffers from profound structural imbalances, because it relies primarily on petroleum revenues in the composition of public revenues in order to contribute to the coverage of public expenditures, thereby posing a risk to them and making them vulnerable to the negative effects of rapid and sudden changes in oil prices in world markets.
The financial performance of the general budget in Algeria in light of changes in international oil prices for the period (1970-2021)
Keywords: موازنة عامة; نفقات عامة; إيرادات عامة; أسعار النفط; جباية بترولية; Public Budget; Public Expenditures; Public Revenues; Oil Prices; Petroleum levy